2007
DOI: 10.1200/jop.0742001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Commercial Reference Laboratory Test Recurrence Score on Decision Making in Early-Stage Breast Cancer

Abstract: Purpose: To investigate whether recurrence score (RS) as determined using a commercial reference laboratory test influences clinicians' treatment recommendations and eventual treatment in patients with early-stage breast cancer. Methods:A retrospective analysis was performed on 74 patients from a community-based oncology practice with estrogen receptor (ER) -positive, lymph node (LN) -negative stage I or II breast cancer for which RS was obtained. Demographic and pathology information was extracted from medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 14 publications
4
73
1
1
Order By: Relevance
“…Several other studies have similarly determined RS changes adjuvant treatment recommendations by 18%-44% [25][26][27][28][29]. Moreover, the most common change in recommendations was from chemotherapy plus hormonal therapy to hormonal therapy alone.…”
Section: Discussionmentioning
confidence: 93%
“…Several other studies have similarly determined RS changes adjuvant treatment recommendations by 18%-44% [25][26][27][28][29]. Moreover, the most common change in recommendations was from chemotherapy plus hormonal therapy to hormonal therapy alone.…”
Section: Discussionmentioning
confidence: 93%
“…In this cohort 46 (48%) results were categorized as Low risk (<18), 30 (31%) were Intermediate risk (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 20 (21%) had High risk (!31) results (Table II). A sizable proportion of both N0 and Nþ patients were classified as Low risk.…”
Section: Patients and Tumor Characteristicsmentioning
confidence: 99%
“…Multiple studies have shown that use of the Oncotype DX Breast Cancer Assay affects treatment recommendations [14][15][16][17][18][19][20][21][22][23][24][25][26]. These studies demonstrated that analysis of treatment decisions before and after receipt of Recurrence Score information showed approximately a 30% decrease in chemotherapy recommendations [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of personalized cancer care, much of the extant literature explores gene-expression profiling in the adjuvant and neo-adjuvant breast cancer setting (eg, Oncotype DX, Mammaprint). [17][18][19][20] Findings from this literature point to broad enthusiasm about the potential to 'personalize' care 17,21,22 and reduce uncertainty. 20,23 There is also, however, some evidence of patient confusion regarding the meaning of test results (eg, whether germline or somatic variants are identified).…”
Section: Introductionmentioning
confidence: 99%